Implementation and effectiveness evaluation of environmental protection measures under sustainable supply chain planning - Yu, Feng (International Journal of Global Economics and Management, 2024)
This paper aims to discuss the implementation and effectiveness evaluation of environmental protection measures under sustainable supply chain planning. Firstly, the background and importance of sustainable supply chain management are introduced, and the role of environmental protection measures in supply chain is expounded. Then the selection and implementation of environmental protection measures are discussed in detail, including classification, selection criteria and implementation methods and methods. Then the evaluation method, including the setting of evaluation index and the application of evaluation tools, is expounded. Through case analysis, the implementation cases of environmental protection measures under specific sustainable supply chain planning are presented and their effects are evaluated. The impact of the implementation of environmental protection measures on sustainable supply chain management, as well as the challenges and problems in the implementation process are discussed and analyzed. Finally, the paper summarizes the research results and puts forward some suggestions on the implementation of environmental protection measures under sustainable supply chain planning, aiming at providing guidance and inspiration for practice. Through this study, we can better understand and apply environmental protection measures in sustainable supply chain management, and promote enterprises to achieve sustainable development goals in practice.